2022
DOI: 10.3389/fnut.2022.933343
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aging on food consumption in rural China: Implications for dietary upgrading and health improvement

Abstract: BackgroundThe issue of population aging in rural China is getting profound; nevertheless, its impact on food consumption has not been well evaluated. This study aims to examine the relationship between rural aging and family food consumption in rural China.Materials and methodsUsing the statistical yearbook data and the nationally representative household-level data from the China Rural Fixed Observation Points, this study compares the evolution of food consumption between rural and urban residents from 1985 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…As people get older, their awareness of consuming safe and healthy food increases, therefore they tend to keep reading food labels on the product packaging. Gao et al (2022) also agree that the aging population increases the demand for certain foods such as poultry and eggs. However, it should be noted that age structure has no significant effect on food consumption in the UK, with race being the only important factor (Astbury et al, 2019).…”
Section: Resultsmentioning
confidence: 86%
“…As people get older, their awareness of consuming safe and healthy food increases, therefore they tend to keep reading food labels on the product packaging. Gao et al (2022) also agree that the aging population increases the demand for certain foods such as poultry and eggs. However, it should be noted that age structure has no significant effect on food consumption in the UK, with race being the only important factor (Astbury et al, 2019).…”
Section: Resultsmentioning
confidence: 86%
“…Lastly, the findings indicating a faster increase in frailty among female residents has highlighted the gender-specific dynamics influencing dietary habits and health outcomes among Chinese older adults. The traditional gender roles and responsibilities in Chinese society may contribute to dietary habits and health behaviors among older adults [30]. Women, particularly in older generations, often bear the responsibility for meal preparation and family caregiving, leading to differential dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…As such, exploring potential rural/urban and gender differences in this relationship offers valuable insights into the nuanced interplay. Studies have shown that rural older adults in China tend to have a lower consumption of animalbased foods, including meat, eggs, and dairy products, compared to their urban counterparts [30]. This disparity in dietary patterns may be attributed to factors such as limited access to markets, lower socioeconomic status, and adherence to traditional dietary practices in rural areas.…”
Section: The Context Of China: Differences By Hukou Status and Gendermentioning
confidence: 99%